Virulence Factors and Antimicrobial Resistance Profile of Escherichia coli Isolated from Nursery Piglets and Drinking Water - Malgarin, Carolina Maciel; Takeuti, Karine Ludwig; Lara, Anne Caroline de; Barcellos, David Emilio Santos Neves de (Acta Scientiae Veterinariae, 2018)
Background: One of the most frequent health problems in the swine industry is the post-weaning diarrhea in nursery pigs, which leads to significant losses due to weight loss, dehydration, cost of medication and mortality. Escherichia coli (E. coli) is one of the main bacterial agents of the post-weaning diarrhea. To investigate the possibility of enterotoxigenic E. coli (ETEC) transmission through drinking water to nursery piglets, the objective of this study was to isolate, characterize by virulence factors, and compare the antimicrobial resistance profiles of E. coli from drinking water samples in nurseries and from rectal swabs of their piglets presenting post-weaning colibacillosis. Materials, Methods & Results: Fifteen rectal swabs from diarrheic piglets in their first three weeks after weaning and one water sample were collected from each of ten nurseries located in Rio Grande do Sul State, south of Brazil. After enrichment with a commercial broth medium, water samples were cultured in blood agar, as well as the rectal swab samples, and the characteristic colonies were identified by standard biochemical analysis. Following isolation and identification of E. coli, the colonies from water samples and their corresponding piglets’ samples were characterized by multiplex PCR in order to determine specific ETEC fimbria and toxin genes. Finally, all E. coli isolates were submitted to antimicrobial susceptibility testing. Virulence factors and antimicrobial sensitivity could then be compared between water and piglets’ samples. The difference in the antimicrobial resistance frequency for each of the sample groups were compared using the multi comparison test. E. coli was isolated in four out of the ten water samples, although none of the water samples presented ETEC virulence factors. From 60 rectal swab samples (15 from each of the four positive farms with E. coli isolated from water samples), 21 E. coli were isolated and seven demonstrated characteristic ETEC virulence factors. The fimbriae exhibited in higher frequency were F18 (62.5%) and F4 (25%) and the toxins were STb (100%) and STaP (75%). E. coli isolated from water samples presented higher resistance to the antimicrobials apramycin, florfenicol, lincomycin, lincomycin+spectinomycin, oxytetracycline, and sulfamethoxazole+trimethoprim; it did not present resistance to colistin and fosfomycin. The seven ETEC from rectal swab samples presented a higher resistance to lincomycin, and lower resistance frequency to fosfomycin. The other 14 E. coli non-ETEC from rectal swab samples presented a higher resistance to florfenicol and no resistance to colistin. Discussion: Enterotoxigenic E. coli is an important agent causing post-weaning colibacillosis, although, differently from other studies, this experiment did not find the agent in most of the sampled animals. In contrast to other authors, ETEC was not found in water, as the development of its virulence factors may depend on conditions presented exclusively in the animal. By the results we can conclude that, although E. coli was isolated from the drinking water, it was not a significant mechanism for nursery piglets’ infection with ETEC in this experiment. The samples analyzed presented a wide range of resistance to different antimicrobials, including multi-resistance. In some cases, E. coli found in water presented different antimicrobial profile from the bacterium found in the rectal swab samples. Enterotoxigenic E. coli was susceptible to fosfomycin and its use may represent a prudent antimicrobial choice to the swine industry.